Development of E-LKPD Project Based Learning Using Liveworksheet Integrated with Creative Thinking Skills - Seputri, Vika; Zurweni, Zurweni; Yusnaidar, Yusnaidar (Jurnal Inovasi Pembelajaran Kimia, 2025)
Reaction rate material involves both realistic and abstract concepts that require visualization and experimentation to better understand the influencing factors. Therefore, the use of a Project-Based Learning (PjBL) model is essential to connect theoretical knowledge with real-world contexts, enabling the creation of innovative and effective learning products that foster students’ creative thinking skills. This study aims to develop an e-LKPD using Liveworksheets based on PjBL for reaction rate material and to evaluate its effect on students’ creative thinking. The research employs the Lee and Owens Research and Development model using interviews, questionnaires, and pre-test–post-test instruments. Validation results from material and media experts indicate a high level of feasibility, while teacher assessments and student responses show strong satisfaction. The pre-test and post-test results reveal a significant improvement in creative thinking skills, with an N-Gain score of 0.6502. Overall, the developed e-LKPD is conceptually valid, practically applicable, and effective in enhancing creative thinking in chemistry learning, particularly in understanding reaction rate concepts.